2002
DOI: 10.1128/mcb.22.24.8467-8477.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPase/Rho Kinase Negatively Regulates Endothelial Nitric Oxide Synthase Phosphorylation through the Inhibition of Protein Kinase B/Akt in Human Endothelial Cells

Abstract: Endothelial nitric oxide synthase (eNOS) is an important regulator of cardiovascular homeostasis by production of nitric oxide (NO) from vascular endothelial cells. It can be activated by protein kinase B (PKB)/Akt via phosphorylation at Ser-1177. We are interested in the role of Rho GTPase/Rho kinase (ROCK) pathway in regulation of eNOS expression and activation. Using adenovirus-mediated gene transfer in human umbilical vein endothelial cells (HUVECs), we show here that both active RhoA and ROCK not only dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
327
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(347 citation statements)
references
References 53 publications
(62 reference statements)
16
327
3
1
Order By: Relevance
“…Interestingly, glucose-induced elevation of protein kinase C seems to be mediated by oxidative stress in rabbit CC smooth muscle cells [21]. Furthermore, Rho-kinase protein expression is increased in diabetic corporal tissue, and the RhoA/Rho-kinase signalling pathway plays an important role in the reduction of NO synthesis through eNOS suppression [22,23]. In the diabetic rat penile crura, ICP is markedly decreased, and the gene expression levels of apoptotic factors, such as Bak and Bax, are increased [24].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, glucose-induced elevation of protein kinase C seems to be mediated by oxidative stress in rabbit CC smooth muscle cells [21]. Furthermore, Rho-kinase protein expression is increased in diabetic corporal tissue, and the RhoA/Rho-kinase signalling pathway plays an important role in the reduction of NO synthesis through eNOS suppression [22,23]. In the diabetic rat penile crura, ICP is markedly decreased, and the gene expression levels of apoptotic factors, such as Bak and Bax, are increased [24].…”
Section: Discussionmentioning
confidence: 99%
“…105 Activation of the RhoA/ROCK pathway impairs NO bioavailability through inhibition of eNOS mRNA stability, eNOS posphorylation at Ser 1177 and the Akt/PI3K pathway and enhancement of eNOS phosphorylation at Thr495. [106][107][108] Endothelial function and hypertension in aging Y Higashi et al Several investigators have shown an interaction between the RhoA/ ROCk pathway and ROS. 109,110 Indeed, ROS induced by hyperglycemia enhances ROCK activity, leading to atherothrombogenesis through an increase in expression of plasminogen activator inhibitor-1 in vascular endothelial cells.…”
Section: Tetrahydrobiopterin (Bh 4 )mentioning
confidence: 99%
“…Rho kinase is implicated in the pathophysiology of atherosclerosis (Miyata et al, 2000), myocardial infarction, and hypertension (Uehata et al, 1997). Activation of Rho kinase in endothelial cells under hypoxic conditions (Wolfrum et al, 2004) has been related to the mechanism responsible for the downregulation of eNOS during and after ischemia (Takemoto et al, 2002;Ming et al, 2002;Wolfrum et al, 2004;Jin et al, 2006).…”
Section: Rho Kinase (Rock)-inhibitorsmentioning
confidence: 99%